In-Session-Reflective-Functioning in Anorexia Nervosa: An Analysis of Psychotherapeutic Sessions of the ANTOP Study - Zeeck, Almut; Taubner, Svenja; Gablonski, Thorsten C.; Lau, Inga; Zipfel, Stephan; Herzog, Wolfgang; Wild, Beate; Friederich, Hans-Christoph; Resmark, Gaby; Giel, Katrin; Teufel, Martin; Burgmer, Markus; et al. (Frontiers in Psychiatry, 2022)
Objective Previous research suggests that patients with anorexia nervosa (AN) show an impaired capacity to mentalize (reflective functioning, RF). RF is discussed as a possible predictor of outcome in psychotherapeutic processes. The study aimed to explore RF in sessions of patients with AN and its association with outcome and type of treatment. Methods A post-hoc data analysis of selected cases from a randomized trial on outpatient psychotherapy for AN was conducted. Transcripts from 84 sessions of 28 patients (early phase, middle phase, and end of treatment) were assessed using the In-Session-Reflective-Functioning-Scale [14 cognitive-behavior therapy, enhanced (CBT-E); 14 focal psychodynamic therapy (FPT); 16 with good, 12 with poor outcome after 1 year]. Relations between the level of RF, type of treatment, and outcome were investigated using mixed linear models. Additionally, associations with depressive symptoms, weight gain, and therapeutic alliance were explored. Results Mean in-session RF was low. It was higher in FPT when compared to CBT-E treatments. The findings point to an association between RF increase and a positive outcome. An increase in BMI in the first half of treatment was associated with higher subsequent in-session RF. There was no association between RF and depressive symptoms or the therapeutic alliance. Discussion Patients with AN show a low capacity to mentalize in sessions, which seems to be at least partly dependent on the degree of starvation. The results suggest a possible relationship between an increase in in-session RF and outcome, which has to be replicated by further studies.